A Randomized Trial of Intravenous Thyroxine for Brain-Dead Organ Donors With Impaired Cardiac Function. (March 2020) - Dhar, Rajat; Stahlschmidt, Emily; Marklin, Gary
Rationale: Brain death (BD) precipitates cardiac dysfunction impairing the ability to transplant hearts from eligible organ donors. Retrospective studies have suggested that thyroid hormone may enhance myocardial recovery and increase hearts transplanted. We performed a randomized trial evaluating whether intravenous thyroxine (T4) improves cardiac function in BD donors with impaired ejection fraction (EF). Methods: All heart-eligible donors managed at a single-organ procurement organization (OPO) underwent protocolized fluid resuscitation. Those weaned off vasopressors underwent transthoracic echocardiography (TTE) within 12 hours of BD and, if EF was below 60%, were randomized to T4 infusion or no T4 for 8 hours, after which TTE was repeated. Results: Of 77 heart-eligible donors, 36 were weaned off vasopressors. Ejection fraction was depressed in 30, of whom 28 were randomized to T4 (n = 17) vs control (n = 11). Baseline EF was comparable (45%, interquartile range [IQR] 42.5-47.5 vs 40%, 40-50, P = .32). Ejection fraction did not improve more with T4 (10%, IQR 5-15 vs 5%, 0-12.5, P = .24), although there was a trend to more hearts transplanted (59% vs 27%, P = .14). This difference appeared to be accounted for by more donors with a history of drug use in the T4 group, who exhibited greater improvements in EF (15% vs 0% without drug use, P = .01) and more often had hearts transplanted (12 of 19 vs 1 of 9, P = .01). Conclusions: In this small randomized study of BD donors with impaired cardiac function, T4 infusion did not result in greater cardiac recovery. A larger randomized trial comparing T4 to placebo appears warranted but would require collaboration across multiple OPOs.